A preliminary study on third tone sandhi in Malaysian Mandarin / Poh Shin Chiew - Poh, Shin Chiew (2021)
Mandarin Chinese language has increased in importance among the Chinese community in Malaysia. At present, the Mandarin language is the only medium of instruction in Chinese schools, but it has also become a lingua franca of local Chinese Malaysians of various dialect groups. With the expansion of the Global Chinese concept, numerous studies have been carried out on the Mandarin language used in Malaysia (henceforth, Malaysian Mandarin). These studies have mainly focused on lexical and syntactic aspects rather than on the phonetic system of Malaysian Mandarin. This could be because many researchers consider the standard spoken form of Malaysian Mandarin similar to Standard Mandarin, although they are different. To better understand the development of the sound systems in regional Mandarin varieties, this paper investigates Malaysian Mandarin, specifically the standard spoken variety, by examining the acoustic realisation of third tone sandhi, a well-known Mandarin language tonal variation phenomenon. Forty-four Malaysian Chinese undergraduate students have been selected as speakers of the standard spoken variety. A nursery rhyme consisting of nineteen third tone (T3) syllables was used as the reading material to analyse the effect of different prosodic and syntactic structures on T3 realisation. The findings indicated that generally, the T3 sandhi phenomena in Malaysian Mandarin match Standard Chinese's sandhi rule. However, the acoustic realisation of T3 in terms of pitch contour and voice quality showed some differences. The implementation of T3 sandhi is also affected by the syntactic and rhythmic structure if a disyllabic or trisyllabic T3 sequence occurs across two feet. The findings suggest that the prosodic structure in the standard spoken form of Malaysian Mandarin may be developing differently from Standard Mandarin.